Trends of the incidence rate of Hepatitis C in Changsha, China, 2005 to 2023 and Its Prediction to 2025 - Shuilian Chen; Ping Zeng; Kewei Yang; Xixing Zhang; Xuewen Yang; Yinzhu Zhou (Journal of Infection in Developing Countries)
Introduction: Hepatitis C is a globally distributed hepatic disease with a high chronicity rate, posing significant global public health concerns. This research aimed to predict the incidence trend of hepatitis C to guide disease prevention and control.